The effect of turbulence on transitional flow in the FDA’s benchmark nozzle model using large-eddy simulation - Xu,X; Manchester,E (International Journal for Numerical Methods in Biomedical Engineering, 2020)
The Food and Drug Administration's (FDA) benchmark nozzle model has been studied extensively both experimentally and computationally. Although considerable efforts have been made on validations of a variety of numerical models against available experimental data, the transitional flow cases are still not fully resolved, especially with regards to detailed comparison of predicted turbulence quantities with experimental measurements. This study aims to fill this gap by conducting largeeddy simulations (LES) of flow through the FDA's benchmark model, at a transitional Reynolds number of 2000. Numerical results are compared to previous interlaboratory experimental results, with an emphasis on turbulence characteristics. Our results show that the LES methodology can accurately capture laminar quantities throughout the model. In the prejet breakdown region, predicted turbulence quantities are generally larger than high resolution experimental data acquired with laser Doppler velocimetry. In the jet breakdown regions, where maximum Reynolds stresses occur, Reynolds shear stresses show excellent agreement. Differences of up to 4% and 20% are observed near the jet core in the axial and radial normal Reynolds stresses, respectively. Comparisons between viscous and Reynolds shear stresses show that peak viscous shear stresses occur in the nozzle throat reaching a value of 18 Pa in the boundary layer, whilst peak Reynolds shear stresses occur in the jet breakdown region reaching a maximum value of 87 Pa. Our results highlight the importance in considering both laminar and turbulent contributions towards shear stresses and that neglecting the turbulence effect can significantly underestimate the total shear force exerted on the fluid.